Combined Cancer Immunotherapy Against Aurora Kinase A - Kaštánková, Iva; Poláková, Ingrid; Dušková, Martina; Šmahel, Michal (Journal of immunotherapy (Hagerstown, Md., 2016)
Aurora kinase A (AURKA) is a centrosomal protein that is overexpressed in a number of human malignancies and can contribute to tumor progression. As we used this protein as a target of DNA immunization, we increased its immunogenicity by the addition of the PADRE helper epitope and decreased its potential oncogenicity by mutagenesis of the kinase domain. For in vitro analysis of induced immune responses in mice, we identified the Aurka(220-228) nonapeptide representing an H-2Kb epitope. As DNA vaccination against the Aurka self-antigen by a gene gun did not show any antitumor effect, we combined DNA immunization with anti-CD25 treatment that depletes mainly regulatory T cells. Whereas 1 anti-CD25 dose injected before DNA vaccination did not enhance the activation of Aurka-specific splenocytes, 3 doses administered on days of immunizations augmented about 10-fold immunity against Aurka. However, an opposite effect was found for antitumor immunity-only 1 anti-CD25 dose combined with DNA vaccination reduced tumor growth. Moreover, the administration of 3 doses of anti-CD25 antibody alone accelerated tumor growth. Analysis of tumor-infiltrating cells showed that 3 anti-CD25 doses not only efficiently depleted regulatory T cells but also activated helper T cells and CD3(-)CD25(+) cells. Next, we found that blockade of the PD-1 receptor initiated 1 week after the first immunization was necessary for significant inhibition of tumor growth with therapeutic DNA vaccination against Aurka combined with depletion of CD25 cells. Our results suggest that combined cancer immunotherapy should be carefully evaluated to achieve the optimal antitumor effect.
Keywords: receptor interleukinu-2 - alfa-podjednotka; kombinovaná terapie; imunizace; Cell Growth Processes; Epitopes, T-Lymphocyte; monoklonální protilátky; Combined Modality Therapy; HEK293 buňky; regulační T-lymfocyty; epitopy T-lymfocytární; Lymphocyte Activation; Cancer Vaccines; HEK293 Cells; CD8-Positive T-Lymphocytes; aktivace lymfocytů; Immunotherapy; T-Lymphocytes, Regulatory; Animals; Aurora kinasa A; CD8-pozitivní T-lymfocyty; lidé; ženské pohlaví; Aurora Kinase A; Humans; zvířata; myši inbrední C57BL; imunoterapie; protinádorové vakcíny; myši; Mice, Inbred C57BL; Interleukin-2 Receptor alpha Subunit; Antibodies, Monoclonal; Programmed Cell Death 1 Receptor; antigeny CD279; Female; DNA vakcíny; Immunization; Mice; buňky - růstové procesy; H-2 Antigens; Vaccines, DNA; H-2 antigeny